Examining the effect of audit committee attributes on firm financial performance with the moderating role of audit quality: applied study on the Egyptian listed companies of food and beverage sector - Fadali, Dina Sayyid (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
Purpose-the study aims to examine the impact of audit committee attributes on financial performance through audit quality as a moderator. audit committee attributes are measured by its size, independence, financial expertise. financial performance is measured by return on assets, return on equity, return on sales, earnings per share, and Tobin’s q, while audit quality is measured by audit fees. design / methodology / approach-the study utilizes a deductive approach to test hypotheses derived from financial theories using empirical data from 28 companies listed on the Egyptian exchange between 2016 and 2022. correlation and GLS regression analyses were conducted as well as fixed versus random effects were tested using hausman test. findings-the results indicated that audit quality has a significant role in enhancing the relationship between audit committee attributes and financial performance, as many results converted from partially supported to fully supported after adding the moderating effect of audit quality. practical implications-the main implication of this research is showing the impact that could be played by audit quality in the relationship between audit committee attributes and financial performance. research limitations-limitations related to the time frame, and the sample. الغرض-تهدف الدراسة إلى دراسة تأثير سمات لجنة المراجعة على الأداء المالي من خلال جودة المراجعة كوسيط. يتم قياس خصائص لجنة التدقيق من خلال حجمها واستقلاليتها وخبرتها المالية. يتم قياس الأداء المالي من خلال العائد على الأصول، والعائد على حقوق الملكية، والعائد على المبيعات، وربحية السهم، وTobin's Q، بينما يتم قياس جودة التدقيق من خلال رسوم التدقيق. التصميم المنهجية المنهج-تستخدم الدراسة منهجا استنتاجيا لاختبار الفرضيات المستمدة من النظريات المالية باستخدام بيانات تجريبية من ٢٨ شركة مدرجة في البورصة المصرية بين عامي ٢٠١٦ و۲۰٢٢. وتم إجراء تحليلات الارتباط والانحدار GLS بالإضافة إلى التأثيرات الثابتة مقابل التأثيرات العشوائية باستخدام اختبار هاوسمان. النتائج-أشارت النتائج إلى أن جودة المراجعة لها دور كبير في تعزيز العلاقة بين خصائص لجنة المراجعة والأداء المالي، حيث تحولت العديد من النتائج من مدعومة جزئيا إلى مدعومة بالكامل بعد إضافة التأثير المعتدل الجودة المراجعة. الآثار العملية-إن الأثر الرئيسي لهذا البحث هو إظهار التأثير الذي يمكن أن تلعبه جودة التدقيق في العلاقة بين سمات لجنة التدقيق والأداء المالي. قيود البحث-القيود المتعلقة بالإطار الزمني والعينة.